PENGARUH PEMBERIAN KONSENTRASI DAN LAMA PERENDAMAN MENGGUNAKAN EKSTRAK TOMAT TERHADAP VIABILITAS BENIH TERUNG UNGU (Solanum melongena. L.) - Hairunnas, Hairunnas; Saputra, Whin Themas Mico; Syahfutra, Bayu Rahman (Universitas Gajah Putih, 2024)
The need for purple eggplant in Indonesia increases every year so that the productivity of purple eggplant itself must also be increased. Seeds that have superior quality will further support the increase in purple eggplant productivity in Indonesia. One of the drivers in increasing seed viability is the use of Plant Growth Regulators (PGRs) such as those contained in tomato extract which are needed for plant development and growth. Tomato extract contains the hormones auxin, gibberellin and cytokinin. The experimental design used was a factorial design arranged in a factorial Completely Randomized Design (CRD) with 3 replications. The factors studied were Concentration (T) consisting of 3 factors, namely; T1 (20%), T2 (40%), T3 (60%) and Soaking time (P) consisting of 3 factors, namely; P1 (2 hours), P2 (4 hours), P3 (6 hours). The administration of tomato extract had a very significant effect on the parameters of growth potential and germination power, then had no significant effect on the parameters of growth rate and dry germination weight. The soaking time of tomato extract had a very significant effect on growth potential and germination power, then had no significant effect on the parameters of growth rate and dry germination weight. There was no significant interaction between the concentration of tomato extract and the soaking time on the viability of purple eggplant seeds in all observation parameters.